Corpus-based Cognitive Study of the English Translation of Folk Culture in Southern Fujian - Liu, Qi (International Journal of Social Sciences and Public Administration, 2024)
Based on the corpus method, this paper conducts an in-depth study on the cognitive process of foreign translation of folk culture in southern Fujian. By analyzing the relevant corpus of folk culture in southern Fujian, this paper probes into the cognitive difficulties, translation strategies and the influencing factors of translation quality in the process of foreign translation. It is found that the uniqueness and complexity of folk culture in southern Fujian bring challenges to its foreign translation, but appropriate translation strategies can effectively improve the quality. This study provides a useful reference for the external dissemination of folk culture in southern Fujian.